Performance Analysis on Spa Service at Badung and Gianyar Regencies - Laksmiadi Janapriat, Dewa Ayu i; Sukarsa, I Made; Adiputra, Nyoman (E-Journal of Tourism, 2014)
Over the last ten years, spa as one of the products of wellness tourism is growing very fast in Bali, necessitating the development strategy in accordance with the conditions of Bali. The rapid development momentum for the business of spa is opened in Bali, although in the external side of the business will compete with the international trade environment to take advantage and create sustainable economic growth prospects. This will be an opportunity for Bali as a destination spa in the future. In an effort to maintain and continue to develop quality as the best spa destinations in the world, we need the right strategy to make the creation and supporting product innovation spa in Bali. This study aims to create an integrated assessment of the extent of the influence of the utilization of natural resources, human resources and local knowledge of the existence and essence of spa in Bali and methods for utilizing natural resources, human resources and local knowledge of Bali on development of spa in Bali. Research design and methods of approach to the problem that are done in this study using descriptive design, where the planning and execution of research conducted in the form of field data are collected in the form of surveys, questionnaires and statistical data processing. The target population in this study is divided into three, namely: the company or a place that offers spa services, spa services supporting manufacturers and both foreign and domestic tourists who use the services of spa services in Badung and Gianyar, by assuming the two districts can represent the tourist population to Bali. Based on several case studies found that the performance of spa services in terms of utilization of natural resources, human resources, and local wisdom of Bali, particularly in terms of (1) the atmosphere (ambience), (2) equipment and design, (3) the qualifications and skills of the therapist, (4 ) treatment menu, and (5) the quality of services as a whole has shown good performance. Consumer expectations of the spa service indicators in terms of utilization of natural resources, human resources, and local wisdom of Bali, particularly in terms of (1) the atmosphere (ambience), (2) equipment and design, (3) the qualifications and skills of the therapist, ( 4). The treatment menu, and (5) the quality of services (service) as a whole have demonstrated the value of important categories.
Keywords: Spa, local natural resources, development, Bali